2021
DOI: 10.3389/feart.2021.771316
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Linked Polymer Soil Stabilizer for Hillslope Conservation on the Loess Plateau

Abstract: The soil of the Loess Plateau is highly susceptible to erosion due to its distinct loess structure with poor water stability and disintegrates easily. Previous research has focused on improving soil strength without considering stability and ecological performance. Comprehensive improvements may be achieved by cross-linked polymers (CLPs), but their effect on loess structure remains unclear. In the present study, we investigate CLPs as a new organic soil stabilizer to improve soil aggregate stability. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Pu et al 34 showed that polymers could reinforce loess strength. Zhang et al 35 indicated that polymers could improve the anti-disintegration property and water retention capacity of loess. In addition, XG could increase the fatigue life of soil 36 and reduce the rheological properties, permeability, and dispersion of soil 37 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Pu et al 34 showed that polymers could reinforce loess strength. Zhang et al 35 indicated that polymers could improve the anti-disintegration property and water retention capacity of loess. In addition, XG could increase the fatigue life of soil 36 and reduce the rheological properties, permeability, and dispersion of soil 37 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The soil-water characteristic curve can reflect different soils' water holding and releasing characteristics. It can be used to simulate the unsaturated permeability law [1][2][3][4][5][6][7], the shear strength of soil [8][9][10], the water migration in soil, the influence of water content change in soil on the mechanical properties, and the composition model of soil [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the loess slope treatment with the traditional soil stabilizer, if the rainfall is too concentrated or continuous, the slope surface is easy to be washed away, resulting in a poor slope protection effect, as shown in Figure 1. In addition, for some traditional slope protection materials, the amount added to the slope protection is about 2%-10% [20][21][22], while the Consolid soil stabilizer can achieve the purpose of elimination of loess collapsibility, water erosion prevention, and slope protection when the amount is relatively small, which is beneficial to environmental protection. According to the characteristics of the fragile ecological environment, serious water and soil loss, and prone to geological disasters in this area, it is proposed to apply the Consolid stabilizer to ecological slope protection.…”
Section: Introductionmentioning
confidence: 99%